(untitled) (Research, Society and Development, 2021)
The mesoinvertebrates cause changes in the physical and chemical properties of organic matter during the composting process. They are excellent recyclers of organic matter. The aim of this study was to evaluate the density and diversity of mesoinvertebrates in an aerobic treatment system for home organic solid waste. The work carried out in Campina Grande, state of Paraíba, Brazil, followed the principles of experimental research. Solid organic waste was collected in 46 residences, previously segregated in the generating source. For 15 weeks the system was monitored daily. During composting, 1.258 individuals belonging to six orders were collected: Diptera (88.5%), Mesostigmata (5.5%), Coleoptera (2.4%), Isopoda (2.4%), Araneae (0.6% ) and Orthoptera (0.6%). In the composting process, three distinct phases were observed, in which the species were differentiated. It was found that during the treatment system for household solid organic waste, there is considerable participation of organisms that act in the different phases of treatment, correlating with physical-chemical changes and influencing the functioning of the entire system.